2022
DOI: 10.3389/fimmu.2022.868523
|View full text |Cite
|
Sign up to set email alerts
|

Three Models of Vaccination Strategies Against Cryptococcosis in Immunocompromised Hosts Using Heat-Killed Cryptococcus neoformans Δsgl1

Abstract: Vaccines are one of the greatest medical accomplishments to date, yet no fungal vaccines are currently available in humans mainly because opportunistic mycoses generally occur during immunodeficiencies necessary for vaccine protection. In previous studies, a live, attenuated Cryptococcus neoformans Δsgl1 mutant accumulating sterylglucosides was found to be avirulent and protected mice from a subsequent lethal infection even in absence of CD4+ T cells, a condition most associated with cryptococcosis (e.g., HIV)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 71 publications
1
22
0
Order By: Relevance
“…Overall, these data show that 1 dose of HK A. fumigatus Δ sglA conidia was sufficient to confer complete host protection in corticosteroid-treated mice and induce protective host immunity necessary to clear the WT strain from the lungs. These data also confirmed the results of previous studies in which an HK C. neoformans Δ sgl1 strain completely protected immunocompromised mice from a lethal WT challenge ( 33 ), suggesting that an HK vaccine formulation enriched in SGs could be a valuable option for protecting individuals at risk of developing invasive cryptococcosis and aspergillosis.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Overall, these data show that 1 dose of HK A. fumigatus Δ sglA conidia was sufficient to confer complete host protection in corticosteroid-treated mice and induce protective host immunity necessary to clear the WT strain from the lungs. These data also confirmed the results of previous studies in which an HK C. neoformans Δ sgl1 strain completely protected immunocompromised mice from a lethal WT challenge ( 33 ), suggesting that an HK vaccine formulation enriched in SGs could be a valuable option for protecting individuals at risk of developing invasive cryptococcosis and aspergillosis.…”
Section: Resultssupporting
confidence: 90%
“…But this should not be a problem because only one administration of either the autoclaved or boiled Δ sglA conidia was sufficient for complete protection of the host. This was not observed in studies using HK C. neoformans Δ sgl1 conidia, where 2 doses of HK conidia were necessary to obtain 100% protection, while 1 dose conferred 70% protection in immunodeficient mice ( 33 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We observed complete (100%) host protection, suggesting that C. neoformans Δ sgl1 mutant can be used as a live, attenuated vaccine 32 . Subsequent studies showed that C. neoformans Δ sgl1 provided complete host protection even during CD4 + T cell deficiency 41 , 42 . We also identified that in order to be protective, C. neoformans Δ sgl1 must display on its surface certain antigenic capsular components, such as glucuronoxylomannan (GXM), because a mutant strain accumulating SGs but lacking the capsule (Δ cap59 Δ sgl1 ) was no longer protective 36 , suggesting that SGs may act as an adjuvant to GXM.…”
Section: Introductionmentioning
confidence: 99%